2005
DOI: 10.1086/429631
|View full text |Cite
|
Sign up to set email alerts
|

Mannose-Binding Lectin in Severe Acute Respiratory Syndrome Coronavirus Infection

Abstract: Little is known about the innate immune response to severe acute respiratory syndrome (SARS) coronavirus (CoV) infection. Mannose-binding lectin (MBL), a key molecule in innate immunity, functions as an anteantibody before the specific antibody response. Here, we describe a case-control study that included 569 patients with SARS and 1188 control subjects and used in vitro assays to investigate the role that MBL plays in SARS-CoV infection. The distribution of MBL gene polymorphisms was significantly different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
300
1
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(319 citation statements)
references
References 47 publications
10
300
1
8
Order By: Relevance
“…In vitro addition of exogenous MBL (5-fold excess) increased C3 deposition on yeasts as well as their uptake by phagocytes. Our results are in agreement with the binding of MBL to C. albicans described previously (32,33), also reporting a MBL-dependent enhancement of C3 deposition and decrease of disseminating candidiasis in mice upon MBL administration. MBL replacement therapy as appropriate (adjuvant) treatment has been suggested for patients with MBL deficiency and disseminated candidiasis.…”
Section: Discussionsupporting
confidence: 93%
“…In vitro addition of exogenous MBL (5-fold excess) increased C3 deposition on yeasts as well as their uptake by phagocytes. Our results are in agreement with the binding of MBL to C. albicans described previously (32,33), also reporting a MBL-dependent enhancement of C3 deposition and decrease of disseminating candidiasis in mice upon MBL administration. MBL replacement therapy as appropriate (adjuvant) treatment has been suggested for patients with MBL deficiency and disseminated candidiasis.…”
Section: Discussionsupporting
confidence: 93%
“…31 Individuals homozygous for the p.D120G mutation have no MBL pathway activity. 20 Except for this situation we surprisingly find no correlation between MASP-2 concentrations and MBL pathway activity.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Chlamydia pneumoniae and Chlamydia psittaci are bound by MBL with inhibition of their growth in cell culture, albeit at much higher inhibitory concentrations than for Chlamydia trachomatis [25] . Pseudomonas aeruginosa , an important pathogen in cystic fibrosis (CF), was initially not thought to be bound by MBL in studies using flow cytometry [19] .…”
Section: Mbl Binds To Many Respiratory Pathogensmentioning
confidence: 99%
“…Two case control studies of Chinese patients showed an association between carriage of the B variant MBL2 allele, the only MBL2 structural variant found in the Chinese population, and predisposition to SARS [4,50] . There was no association between low MBL2 haplotypes and death due to SARS.…”
Section: Respiratory Viral Infectionsmentioning
confidence: 99%